A Review on Vital Pulp Therapy in Primary Teeth - Parisay, Iman; Ghoddusi, Jamileh; Forghani, Maryam (Iranian Endodontic Journal, 2014)
Maintaining deciduous teeth in function until their natural exfoliation is absolutely necessary. Vital pulp therapy (VPT) is a way of saving deciduous teeth. The most important factors in success of VPT are the early diagnosis of pulp and periradicular status, preservation of the pulp vitality and proper vascularization of the pulp. Development of new biomaterials with suitable biocompatibility and seal has changed the attitudes towards preserving the reversible pulp in cariously exposed teeth. Before exposure and irreversible involvement of the pulp, indirect pulp capping (IPC) is the treatment of choice, but after the spread of inflammation within the pulp chamber and establishment of irreversible pulpitis, removal of inflamed pulp tissue is recommended. In this review, new concepts in preservation of the healthy pulp tissue in deciduous teeth and induction of the reparative dentin formation with new biomaterials instead of devitalization and the consequent destruction of vital tissues are discussed.